Implementation of the Integrated Service Concept in Strengthening Child Protection Policy in Banda Aceh City - Muazzinah Muazzinah; Cut Zamharira; Zakki Fuad Khalil; Khalida Ulfa; Putri Marzaniar; Fathurrahman Al-Ayubi; Heri Maulana (Journal Public Policy, 2026)
This study aims to analyze the implementation of integrated service mechanisms in strengthening child protection policies in Banda Aceh City and to identify the main challenges affecting policy effectiveness. Child protection remains a critical public policy issue in Indonesia, particularly in Banda Aceh where cases of violence against children continue to attract public concern. This research employs a qualitative design using a phenomenological and normative approach to examine both the legal framework and the experiences of key stakeholders involved in policy implementation. Data were collected through in-depth interviews with government officials, members of the local parliament, non-governmental organizations, community leaders, and supporting institutions, complemented by document analysis. The data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal a significant gap between policy design (“policy on paper”) and practical implementation (“policy in action”). Three major systemic problems were identified. First, structural failure is reflected in the absence of a specific municipal regulation governing child protection. Second, resource failure is evident in the limited availability of professional personnel within the UPTD PPA. Third, coordination failure leads to institutional fragmentation and weak inter-agency collaboration. Consequently, integrated child protection services remain largely symbolic and have not yet achieved optimal effectiveness.